The Slain Wood : Papermaking and Its Environmental Consequences in the American South - Boyd, William, 1967- (Book collections on Project MUSE., 2015)
When the paper industry moved into the South in the 1930s, it confronted a region in the midst of an economic and environmental crisis. Entrenched poverty, stunted labor markets, vast stretches of cutover lands, and severe soil erosion prevailed across the southern states. By the middle of the twentieth century, however, pine trees had become the region's number one cash crop, and the South dominated national and international production of pulp and paper based on the intensive cultivation of timber. In The Slain Wood, William Boyd chronicles the dramatic growth of the pulp and paper industry in the American South during the twentieth century and the social and environmental changes that accompanied it. Drawing on extensive interviews and historical research, he tells the fascinating story of one of the region's most important but understudied industries. [This book] reveals how a thoroughly industrialized forest was created out of a degraded landscape, uncovers the ways in which firms tapped into informal labor markets and existing inequalities of race and class to fashion a system for delivering wood to the mills, investigates the challenges of managing large papermaking complexes, and details the ways in which mill managers and unions discriminated against black workers. It also shows how the industry's massive pollution loads significantly disrupted local environments and communities, leading to a long struggle to regulate and control that pollution. -- Inside jacket flap.